Counter-Hegemonic Visions of Self-Respect in a Novel: Ramamirthammal's Challenge to Indian Nationalism. Issue 2 (December 2020) - Sriharan, Sitharthan
Periyar's Self-Respect Movement challenged the ideological hegemony of the Indian Independence struggle by demanding that equality between sexes and eradicating caste be put on an equal footing with national liberation. The author analyses a chapter in a novel written by Muvalur Ramamirthammal, a reformer from a devadasi community, who joined the Self-Respect Movement and became an ardent abolitionist of the devadasi system. In a dialogue between an ex-devadasi, who is represented as a Self-Respect activist, and a Brahmin man with Indian nationalist views, the former devadasi highlights the Self-Respect Movement's definition of modern citizenship based on the principles of self-respect and dignity of all beginning with women. The article concludes by discussing the novel's wider connection to the Self-Respect Movement and why further research on both respectively is crucial.